2016
DOI: 10.1111/jfcj.12081
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effectiveness of a Juvenile Drug Court: Comparisons to Traditional Probation

Abstract: Juvenile Drug Courts have been in operation in the United States for over 20 years, yet their effectiveness and design have been challenged throughout the literature. Using data collected from a Juvenile Drug Court (JDC) in Southeast Texas, this project sought to determine if the JDC intervention reduced recidivism compared to a comparison sample of juvenile offenders. Results indicate that the recidivism rates of participants in the JDC were lower than the comparison group, suggesting that the Drug Court inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Among youth receiving drug court services, juvenile offenders who had been involved with illegal substances were less likely to recidivate. This finding is consistent with Hypothesis 4 and similar to prior research showing that juveniles with drug abuse histories are less likely to abuse illegal substances as well as engage in other misdemeanor crimes associated with drug use while receiving JDC treatment (Rodriguez & Webb, 2004; Gummelt & Sullivan, 2016). Similar to Rodriguez and Webb (2004), this finding is also consistent with meta‐analyses concluding that JDC are an effective solution for drug/alcohol involved youth (van Wormer & Lutze, 2011; Stein et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…Among youth receiving drug court services, juvenile offenders who had been involved with illegal substances were less likely to recidivate. This finding is consistent with Hypothesis 4 and similar to prior research showing that juveniles with drug abuse histories are less likely to abuse illegal substances as well as engage in other misdemeanor crimes associated with drug use while receiving JDC treatment (Rodriguez & Webb, 2004; Gummelt & Sullivan, 2016). Similar to Rodriguez and Webb (2004), this finding is also consistent with meta‐analyses concluding that JDC are an effective solution for drug/alcohol involved youth (van Wormer & Lutze, 2011; Stein et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…The exception to this was teen courts: Some studies found positive effects (e.g., Smokowski et al, 2018) and others observed nonsignificant (Norris, Twill, and Kim, 2011) or even negative effects (Wilson et al, 2009). Studies also suggested generally positive outcomes resulting from problem-solving court models, including drug courts (e.g., Gummelt and Sullivan, 2016) and mental health courts (e.g., Behnken, Arredondo, and Packman, 2009).…”
Section: Discussion and Implications For The Los Angeles County Juven...mentioning
confidence: 99%
“…There is also evidence that positive results from drug courts can be maintained over time: A fourth study found that participants had significantly fewer infractions, misdemeanors, and felonies than similar peers on probation over a five-year outcome period (Gummelt and Sullivan, 2016).…”
Section: Drug Courtsmentioning
confidence: 99%
“…These programs usually include identification and referral of youth after adjudication. The intense supervision they provide requires program participants to have frequent contact with the judge, have frequent contact with a probation officer, participate in periodic mandatory drug testing, be involved in substance use treatment, and be involved in school or vocational training (Belenko & Logan, 2003; Gummelt & Sullivan, 2016; Office of Juvenile Justice and Delinquency Prevention, 2016). JDTCs use incentives and sanctions to motivate and sustain desired behavior changes.…”
Section: Therapeutic Jurisprudence and Juvenile Drug Treatment Courtsmentioning
confidence: 99%
“…They are organized around a team approach to case planning and services and having participants advance through a multi‐phase program. Each phase likely offers participants increased rewards and reduced supervision in recognition of improvements with self‐control and decision‐making, reductions in substance use, and increased engagement in prosocial behavior (Belenko & Logan, 2003; Gummelt & Sullivan, 2016).…”
Section: Therapeutic Jurisprudence and Juvenile Drug Treatment Courtsmentioning
confidence: 99%